Sifat Mekanik Edible Film Berbasis Protein dengan Penggunaan Konsentrasi Plasticizer Sorbitol yang Berbeda - Fitri; Fahrullah; Wahid Yulianto (Journal of Microbiology, Biotechnology and Conservation, 2025)
Edible film is a type of biodegradable packaging that can be an alternative to food packaging material to reduce environmental damage and maintain food product’s shelf life, quality, and safety. This research aims to determine the effect of the mechanical properties of protein-based edible film using different concentrations of sorbitol plasticizer on edible film thickness, gelation time, and film microstructure. To make edible films, the research material consists of sorbitol, whey protein, gelatin, distilled water, and silica gel. The research was conducted using a completely randomized design with three sorbitol plasticizer treatments consisting of P1:35%, P2:40%, P3:45%, and three replications. The data were analyzed using Analysis of Variance (ANOVA) and continued with the Duncan Multiple Range Test (DMRT) using the SPSS program. The research results showed that the use of sorbitol plasticizer with different concentrations gave a very significant difference (P<0.01) to P1 and P3, but P2 was not significantly different from the thickness of the edible film. The gelation time did not make a difference (P>0, 05), which is real, but adding different sorbitol to the edible film microstructure can produce varying microstructures. From the research results, the average values for edible film thickness are 0.053, 0.078, and 0.113 mm, while the gelation time produces average values of 19.33, 13.33, and 19 minutes. This research concludes that using different sorbitol concentrations provides a very significant difference in film thickness; however, unlike the gelation time, which does not make a difference, the microstructures produce varying microstructures.